Policy confluences, curricular changes and access to academic knowledge: mapping the structure and content of the Icelandic upper secondary academic curriculum - Jónasdóttir, María; Eiríksdóttir, Elsa; Ragnarsdóttir, Guðrún (Nordic journal of studies in educational policy, 2025)
In this paper, the consequences and manifestations of international policy trends of marketization within education, increasing financial efficiency and competency-based curricular planning are explored, using the Icelandic upper secondary academic curriculum as an example. The academic programmes are to introduce students to varied academic subjects as well as to provide students with a sufficient specialized preparation for higher education. With the general aims to increase flexibility in upper secondary education, encourage more individualistic approaches and accommodate the needs of a more diverse student body, Icelandic upper secondary schools were given substantial curricular authority to design their own academic programmes around certain learner-specific competencies. The aim of the paper is to explore and critically discuss the curricular consequences of the policy changes from the perspective of educational equalities, building on the argument that access to academic knowledge is a matter of social justice. The findings indicate significant difference in the structure and content of the academic programmes that invite questions on students’ access to academic knowledge.